Pembelajaran Konsep Mekanika Fluida Statis Berbantuan Praktikum Virtual Dalam Mengembangkan Keterampilan Berpikir Kritis Mahasiswa Calon Guru Matematika - Dede Trie Kurniawan; Nelli Ma'rifat Sanusi; Nurul Ikhsan Kharimah (Phenomenon : Jurnal Pendidikan MIPA, 2017)
This study aimed to analyze the achievement of critical thinking skills of students throughvirtual lab assisted learning in preservice teachers of mathematics. The method used isweak experiment with the design of the study quot;one group pretest-posttest designquot;. Theresearch was conducted on the subject for the static fluid level mathematics preserviceteachers university sector in the city of Cirebon academic year 2016/2017. The researchsubjects consisted of one class with the number of samples respectively of 23 preserviceteachers of mathematics. The data obtained in this study is data critical thinking skills thatinclude identifying the relevant issues, defines the subject matter, giving the reasons of theexperiment, using a strategy logically, doing the things done tentatively, summarized byconsidering the situation and then decide, answered questions about the facts, report isbased on observations, consider the appropriate procedures, involving a bit of conjecturebased on those events - events and report experimental generalization. Research hypothesistesting is done by using the t test on the N-gain critical thinking skills after learning to usethe virtual lab. The results of data analysis showed critical thinking skills gain of 0.58(moderate). From this analysis it can be concluded that learning-based virtual lab forpreservice teachers of mathematics can significantly improve the critical thinking skills ofpreservice teachers of mathematics. Besides, in general, the students give a positiveresponse to learning to use the virtual lab.